A multi-channel clogging-resistant lab-on-a-chip cell counter and analyzer. (6th January 2016) - Dai, Jie; Chiu, Yu-Jui; Lian, Ian; Wu, Tsung-Feng; Yang, Kecheng; Lo, Yu-Hwa
Abstract: Early signs of diseases can be revealed from cell detection in biofluids, such as detection of white blood cells (WBCs) in the peritoneal fluid for peritonitis. A lab-on-a-chip microfluidic device offers an attractive platform for such applications because of its small size, low cost, and ease of use provided the device can meet the performance requirements which many existing LoC devices fail to satisfy. We report an integrated microfluidic device capable of accurately counting low concentration of white blood cells in peritoneal fluid at 150 μ l min −1 to offer an accurate (<3% error) and fast ( 10 min/run) WBC count. Utilizing the self-regulating hydrodynamic properties and a unique architecture in the design, the device can achieve higher flow rate (500–1000 μ l min −1 ), continuous running for over 5 h without clogging, as well as excellent signal quality for unambiguous WBC count and WBC classification for certain diseases. These properties make the device a promising candidate for point-of-care applications.